MSME Development through Digital Marketing in Lawe Bulan District, Southeast Aceh - Farma Andiansyah; Dicky Zulkarnaen (Business Finence Analyst Co.,, 2024)
Developing MSMEs through digital marketing is crucial in the digital era, especially in remote areas such as Lawe Bulan District, Southeast Aceh. This community service aims to increase the capacity of 10 local MSMEs in adopting digital marketing strategies. The method used is an educational approach through intensive training for a week and direct mentoring. The results showed an increase in participants' understanding of digital marketing from 30% to 65%. Eight out of 10 MSMEs successfully created or updated business accounts on Instagram, 6 MSMEs started creating promotional content, and 3 MSMEs used Instagram's promotional features. The main challenges included limited devices, difficulty understanding analytical metrics, and concerns about online security. Practical solutions were provided for each obstacle. This program successfully provided the basics of digital marketing and sparked MSMEs' interest in adopting digital marketing strategies. However, ongoing mentoring is needed for significant long-term impact.